Open Tension Free Mesh Repair of Inguinal Hernias: The Lichtenstein Technique- 26 Our Experience for Last Ten Years (Journal of Surgical Sciences, 2013)
Objective : Recurrences following hernia repair is one of the significant problem for both patient & surgeon. Open tension free mesh techniques of inguinal hernia repair offers good results. Prosthetic materials have been increasingly used in hernia repair to prevent recurrences. Their use has been associated with several advantages, such as less postoperative pain, rapid recovery and low recurrence rates. Materials and method : In this retrospective study, 1050 tension-free inguinal hernia repairs were performed between January 2001 and December 2010 in various medical institutes including BSMMU, DMCH & some private clinics in Dhaka city, using a polypropylene mesh (Lichtenstein technique). The main outcome measure was early and late morbidity and especially recurrence. Results : Inguinal hernia was indirect in 76 % of cases (798 patients), direct in 22% (231 patients) and of the pantaloon (mixed) type in 2 % (21 patients). Mean patient age was 44.5 years (range, 18 85). Follow-up was completed in 630 patients (60 %) by clinical examination or phone call. The median follow-up period was 2.5 years (range 1 5 years). Seroma and hematoma formation requiring drainage was observed in 25 and 8 patients respectively, while transient testicular swelling occurred in15 patients. Infection was found in 9 patients. Rejection of mesh occurred in 4 patients. There was 6 recurrence of the hernia (in one of these patients with late mesh rejection) (recurrence rate = 0.57 %). Postoperative neuralgia was observed in 25 patients (2.38 %). Conclusion : Lichtenstein tension-free mesh repair of inguinal hernia is a simple, safe, comfortable, effective method. Tension free repair using synthetic meshes have been reported to result in better patient comfort and lower recurrence rates compared with the conventional procedures like Shouldices or Bassinis operation2-4. Therefore it is the preferred method for hernia repair since 1994. DOI: http://dx.doi.org/10.3329/jss.v16i1.14444 Journal of Surgical Sciences (2012) Vol. 16 (1) : 26-29